Sponges (Porifera: Spongillida) as ecological indicators for parasitic protozoans Cryptosporidium and Giardia infective stages in freshwater ecosystems - Frederick R. Masangkay; Renata Manconi; Giovanni D. Milanez; Manas Kotepui; Voravuth Somsak; Jitbanjong Tangpong; Panagiotis Karanis (Ecological Indicators, 2022)
Sponges filter large volumes of water by actively pumping it through their bodies to acquire nutrients, while Cryptosporidium and Giardia are aquatic ecosystems' primary faecal parasitic pollutants. Five aquatic matrices each of surface water (SW), water sediments (WS), substrate-associated biofilms (SAB), as well as five sponges collected from Lake Buhi were investigated for the presence of parasitic protozoan (oo) cysts. Modified Kinyoun's acid-fast stain (MK) was used to detect Cryptosporidium, while immunofluorescence (IFT) staining was employed to detect both Cryptosporidium and Giardia. Scanning Electron Microscopy (SEM) was used to visualize the skeletal sponge structures and simulated contamination with C. parvum oocysts. Aquatic matrices of WS and SAB demonstrated a 20% (3/15) positivity for Cryptosporidium spp. oocysts with MK and IFT. Overall, the study site prevalence of Cryptosporidium spp. oocysts in aquatic matrices were 60% (3/5). Freshwater sponges demonstrated 100% (5/5) Cryptosporidium and 20% (1/5) Giardia (oo) cysts positivity through IFT. Sponges were ascribed to Radiospongilla cfr. philippinensis (Annandale, 1909) based on diagnostic morphotraits of the siliceous skeleton, i.e., megascleres and gemmuloscleres identified under light microscopy (LM) and SEM. Sponges spiked with Cryptosporidium parvum oocysts simulated parasitic protozoan contamination and demonstrated that oocysts could fit through and be trapped within the sponge aquiferous canals. The presence of Cryptosporidium spp. oocysts in aquatic matrices and Cryptosporidium and Giardia spp. (oo) cysts in Radiospongilla cfr. philippinensis demonstrated the contamination of Porifera with infective stages of both parasites. This study submits a promising perspective on the role of freshwater sponges as ecological indicators, i.e. reservoirs and potential biomonitors for the contamination of infective stages of waterborne parasitic protozoans in aquatic ecosystems.